Understanding Infection: A Primer on Animal Models of Periprosthetic Joint Infection - Alexandra I. Stavrakis; Jared A. Niska; Amanda H. Loftin; Fabrizio Billi; Nicholas M. Bernthal (The Scientific World Journal)
Periprosthetic joint infections are devastating complications for patients and for our health system. With growing demand for arthroplasty, the incidence of these infections is projected to increase exponentially. This paper is a review of existing animal models to study periprosthetic infection aimed at providing scientists with a succinct presentation of strengths and weaknesses of available in vivo systems. These systems represent the tools available to investigate novel antimicrobial therapies and reduce the clinical and economic impact of implant infections.